PHIST proteins: at the center of host cell remodeling - Warncke, J; Vakonakis, I; Beck, H (American Society for Microbiology, 2016)
During the asexual cycle, Plasmodium falciparum extensively remodels the human erythrocyte to make it a suitable host cell. A large number of exported proteins facilitate this remodeling process, which causes erythrocytes to become more rigid, cytoadherent, and permeable for nutrients and metabolic products. Among the exported proteins, a family of 89 proteins, called the Plasmodium helical interspersed subtelomeric (PHIST) protein family, has been identified. While also found in other Plasmodium species, the PHIST family is greatly expanded in P. falciparum. Although a decade has passed since their first description, to date, most PHIST proteins remain uncharacterized and are of unknown function and localization within the host cell, and there are few data on their interactions with other host or parasite proteins. However, over the past few years, PHIST proteins have been mentioned in the literature at an increasing rate owing to their presence at various localizations within the infected erythrocyte. Expression of PHIST proteins has been implicated in molecular and cellular processes such as the surface display of PfEMP1, gametocytogenesis, changes in cell rigidity, and also cerebral and pregnancy-associated malaria. Thus, we conclude that PHIST proteins are central to host cell remodeling, but despite their obvious importance in pathology, PHIST proteins seem to be understudied. Here we review current knowledge, shed light on the definition of PHIST proteins, and discuss these proteins with respect to their localization and probable function. We take into consideration interaction studies, microarray analyses, or data from blood samples from naturally infected patients to combine all available information on this protein family.